DYNAMICS OF ADVOCATES' IMMUNITY RIGHTS IN PROVIDING LEGAL AID IN THE INDONESIAN STATE SYSTEM - Kahar Kahar; Retno Wulan (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
In the era of globalization and rapid legal development, the role of lawyers in the Indonesian justice system and the administration of justice becomes increasingly crucial. However, their immunity rights often become the subject of debate within dynamics that affect the legal process. The research aims to examine the dynamics of the relationship between lawyers' immunity rights and moral obligations in the context of providing legal assistance in Indonesia and to evaluate the impact of violations of lawyers' immunity rights on the quality of legal assistance services and public trust in the legal profession in Indonesia. This research will employ a normative legal method with a focus on analyzing legal texts governing lawyers' immunity rights within the Indonesian constitutional framework. Research materials will include legal documents such as laws and regulations, with data analysis techniques involving a deep understanding of the content of legal texts. The research findings indicate that in the practice of law in Indonesia, the relationship between lawyers' immunity rights and moral obligations is highly significant. Lawyers have immunity rights that protect them in providing legal advice without external pressure, but they also have a moral obligation to uphold honesty, integrity, and client confidentiality. The influence of the legal and social environment can also affect how lawyers fulfill their moral obligations. Violations of lawyers' immunity rights in Indonesia have serious implications for the quality of legal assistance provided by lawyers and also damage public trust in the profession. Therefore, it is important for the government, professional organizations, and society to work together to ensure the protection of lawyers' immunity rights so that lawyers can carry out their duties with integrity and high trust, and the public can have faith in a fair and effective legal system. Research recommendations include efforts to enhance lawyers' understanding of the relationship between immunity rights and moral obligations, educating the public about the role of lawyers, and enforcing the law rigorously against violations of lawyers' immunity rights.